The effects of gender inequality on rural households livelihoods diversification : a case study of Sebayeng village, Polokwane, Limpopo Province - Mokgokong, Madikana Jackinah (University of Limpopo (Turfloop Campus), 2010)
Feminist studies show that gender inequality is an impediment for livelihoods diversification among rural households. Whereas women are understood to be the designers, planners and managers of livelihoods for household survival, their roles in diversification of the means of earning a living are generally undermined through a myriad of social and cultural laws, values, norms and beliefs. Despite the publicity, attempts and efforts in redressing gender inequality in a demographic South Africa, the dissertation argues that gender inequality in rural areas has remained persistent, posing an obstacle to the capacity of households to diversify their livelihoods. The study uses survey results from Sebayeng Village in order to demonstrate that the community’s perceptions of women’s roles perpetuate the status quo wherein women’s capacity to diversify livelihoods are undermined. The survey involved 200 households that were sampled through the simple random design. The respondents consisted of 56.5% females and 43.5% males. The survey results demonstrate that gender inequality remains deep in Sebayeng Village and that such inequality negatively affects the ability of households to diversify their livelihoods. Therefore, this study tends to confirm the general principle that gender inequality renders women as unexplored resources in rural development. To that extent, the study concludes that one of the tests for the success in gender transformation in South Africa is in releasing the energies of women in the sphere of livelihoods diversification.
Thesis (M.Admin. (Development)) --University of Limpopo, 2010
Keywords: Gender inequality; 305.4; Women in rural development -- South Africa -- Limpopo Province; Poor women -- developing countries; Sexual division of labor